Area of Plantation Crops to the Contribution of the Plantation Sector in South Halmahera Regency in 2017-2023 - Ruliyanto Syahrain; Fahima Nasar; Muhammad Khotib; Muhammad Kamal (CV. Media Digital Publikasi Indonesia, 2026)
Although not all sub-districts have lost their plantation land, mining activities in the upstream and downstream forest areas have had an indirect impact on the decline in the productivity of the remaining plantation land in the surrounding area. Therefore, this study aims to examine the extent of plantation crops on the contribution of the plantation sector in South Halmahera Regency. This research was conducted in 2024. The design of this study is quantitative research using secondary data sourced from the Central Statistics Agency (BPS). This study itself is for the purpose of testing the hypothesis using a simple linear regression analysis tool. The statistical results show β = 0.119 t = 0.605 sig = ≥ 0.05. This study reveals that the area of plantation crops has no contribution to the plantation sector in South Halmahera Regency. The main causes are many clove and coconut trees have entered the old/damaged plant phase, a very massive surge in investment in the nickel mining sector and the upstream-downstream processing industry and the price of commodities such as copra (coconut processing) and dried cloves at the farmer level which are often uncertain.